Evaluasi Kualitas Website Forum Diskusi Online Menggunakan Metode Webqual 4.0 dan Importance Performance Analysis (Studi Kasus Pada Website Dictio) - Ega Claudia Iqla Azizah; Himawat Aryadita; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dictio is an online discussion group which established to help people for discussing, sharing experiences with communities, sharing knowled and thoughts as well as question & answer more confortable, professional and open. The aim of this research is to know the usability, information quality and service interaction quality on Dictio based on Webqual 4.0 method. Data collection gathered from spreading the questionnaire then analyze the data using descriptive method and Importance Performance Analysis (IPA). As a result, on the usability has 1 indicator goes to quadrant I (main priority), 2 indicators go to quadrant II (preserve achievement), 3 indicators go to quadrants III (low priority) and 2 indicators go to quadrants IV. On information quality has 2 indicators go to quadrants I (main priority), 2 indicators go to quadrants II (preserve achievement), 3 indicators go to quadrants III (low priority). On service interaction quality has 1 indicator goes to quadrant I (main priority), 4 indicators go to quadrants II (preserve achievement), 2 indicators go to quadrants III (low priority). As it shown, the writer recommended an improvement toward the quality based on relevance journal and research.